Improving a New Digital Content Creation Line of Study in Adult Education College - Anttonen, Riikka (My University, 2020)
The topic of the research is digitalization and digital competence frameworks and competence in the digitalized world and programming. Research methods in the thesis are the qualitative research, the review of literature and case study. Used methods in case study are interviews, questionnaire and observation. Research group in the case study are the new Digital Content Creation line of study students. The new Digital Content Creation line of study was designed according to the Digital Competence Framework 2.0 from European Commission. With the questionnaires, students evaluated their digital skills in the beginning of the studies, in the middle of the study year and at the end of the studies. Review of literature was made in researching digitalization and digital frameworks and competence in digitalization and programming. The goal of the action research process was to improve the Digital Content Creation line of study curriculum and programming teaching. According to interviews, the students think that their digital skills have improved very much during the study year. Students have gained good basics to begin to learn more about programming. As a conclusion according to the research and the case study, basic civic skills that everyone should master are determined. Determined skills are: understanding technology, digital tools, privacy and security, communicating through digital technologies, problem solving, updating digital skills, computational thinking, searching and filtering digital information and giving specific instructions.
Keywords: action research, digital content creation, digitalization, teaching programming, digital competence, digital framework, programming framework